Issues on essential elements of formation of e-contract in Malaysia: e-consumers' perspective - Amin, Naemah; Mohd Nor, Roshazlizawati (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
Although e-commerce is growing at a significant rate, a number of stumbling blocks continue to hamper its development. One stumbling block relates to formation of e-contract. There remains uncertainty whether the traditional principles of contract law can be adapted to the needs of electronic contracting. Consequently parties might disagree as to what point and in which country an e-contract is formed. This issue needs to be addressed to boost the integrity of electronic transactions especially in sale of goods since the subsequent rights and liabilities of the contracting parties will depend on whether an agreement has been reached between them. Undeniably, the electronic contract is significantly different from traditional contract which trigger various new legal issues even at the initial stage of the contract. Based on Malaysian legal practice and in comparison with United Nations Commission on International Trade Law (UNCITRAL) Model Law on Electronic Commerce as well as United Kingdom law and European Union’s Directives on e-commerce, this paper seeks to analyze and identify consumer issues concerning the formation of e-contracts. This includes the discussion on the creation of legally enforceable agreement, the appropriateness of the postal rule and its application to e-mail, the need of written contract as well as digital signature and the uncertainty of where and when the e-contract is formed. The paper also examines relevant Malaysian legislation on formation of e-contract including the Contracts Act 1950, Sale of Goods Act 195, Electronic Commerce Act 2006 and the Digital Signature Act 1997 and the adequacy of the existing law in protecting e-consumers.